Bilateral single-system ectopic ureter: When can we avoid bladder neck reconstruction? - Prashant Motiram Mulawkar; Parag Vijayrao Tapre; Pankaj N Maheshwari; Sumeet Gopal Agrawal; Giridhar Shivnarayan Panpaliya (Wolters Kluwer Medknow Publications, 2022)
Bilateral single-system ectopic ureter (BSSEU) is often associated with underdeveloped incompetent bladder neck; hence, to achieve continence, bladder neck reconstruction (BNR) is usually advocated with ureteric reimplantation. Presented here is a 14-year-old girl with BSSEU who achieved continence without BNR. An attempt is made to look at factors that could identify patients in whom BNR could be avoided.